Fair and Equitable Benefit-Sharing in Agriculture Reinventing Agrarian Justice - Tsioumani, Elsa (Taylor & Francis, 2020)
This book explores the emergence and development of the legal concept of fair and equitable benefit-sharing, and its application in agriculture. Drawing on a range of case studies the book examines the emergence of benefit-sharing in international environmental law.